Evaluasi Dimensi Saluran Drainase Pada Kawasan Jalan Rukun, Kelurahan Rapak Dalam, Kota Samarinda - Amalia Istikhomah Qolbiyati; Dhinar Yoga Hanggung Legowo; Tommy Ekamitra Sutarto (Universitas Kristen Immanuel, 2025)
The Rukun Street area in Rapak Dalam Subdistrict is a location frequently affected by flooding. This issue is suspected to be caused by the inadequate dimensions of the existing drainage channels, which are unable to convey runoff efficiently during periods of high rainfall intensity. This study aims to evaluate the adequacy of the existing drainage channel dimensions in handling the stormwater runoff in the area. The evaluation involves determining rainfall intensity and design flood discharge (Q) for return periods of 2, 5, and 10 years, as well as identifying the appropriate drainage dimensions for the area. The analysis results, using the Nakayasu Unit Hydrograph method, show that the design flood discharge on the right segment is Q2: 1.026 m³/s, Q5: 1.467 m³/s, and Q10: 1.758 m³/s. For the left segment, the values are Q2: 1.024 m³/s, Q5: 1.463 m³/s, and Q10: 1.754 m³/s. Redesigning the drainage channels is necessary, as the existing structures cannot accommodate the design flood discharge. The recommended channel dimensions to handle the 10-year return period discharge are 2.23 meters in height and 2.788 meters in width for the right segment, and 1.688 meters in height and 1.923 meters in width for the left segment.